Criminal minor acts : police officer's handbook - Koshy, K (New Delhi, 2004)
The Bureau of Police Research & Development lays down the syllabi for various induction level as well as in-service training course at police training institutions in the country. The volume includes most of the Minor Acts Police officers find useful in their training as well as in the day-to-day functioning, in one volume and with a simple and lucid short commentary
Keywords: Criminal minor act